2013
DOI: 10.2971/jeos.2013.13081
|View full text |Cite
|
Sign up to set email alerts
|

Polishing of optical media by dielectric barrier discharge inert gas plasma at atmospheric pressure

Abstract: In this paper, surface smoothing of optical glasses, glass ceramic and sapphire using a low-power dielectric barrier discharge inert gas plasma at atmospheric pressure is presented. For this low temperature treatment method, no vacuum devices or chemicals are required. It is shown that by such plasma treatment the micro roughness and waviness of the investigated polished surfaces were significantly decreased, resulting in a decrease in surface scattering. Further, plasma polishing of lapped fused silica is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…For plasma post-processing, a plasma source as described in more detail in previous work [38][39][40] was used. This plasma source basically consists of a conical rotation-symmetric high-voltage copper electrode embedded in a plastic housing made of polyoxymethylene (POM).…”
Section: Plasma Post-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…For plasma post-processing, a plasma source as described in more detail in previous work [38][39][40] was used. This plasma source basically consists of a conical rotation-symmetric high-voltage copper electrode embedded in a plastic housing made of polyoxymethylene (POM).…”
Section: Plasma Post-processingmentioning
confidence: 99%
“…In contrast to classical arc discharges, burn-off of the electrode material is moreover reduced or even inhibited, avoiding the deposition of electrode material on the sample surface. In the present work, the plasma treatment duration was 60 s. The impact of such short-term direct DBD plasma post-processing was investigated since it was observed in previous work that applying this type of plasma for merely one minute allows considerable smoothing of optical media [39,40] as well as surface cleaning and an accompanying increase in LIDT of sapphire substrates [16].…”
Section: Plasma Post-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such impact of DBD-plasmas on the roughness of glass surfaces was already reported in previous work. It was shown that, depending on the particular plasma discharge type and the used process gas, both surface smoothing [29] and surface wrinkling [17] can occur. In the present case, the average area roughness S a as well as the root mean square area roughness S q were reduced as a result of the plasma treatment as shown in Figure 4.…”
Section: Plasma Pre-treatmentmentioning
confidence: 99%
“…A lot of models to describe the kinetics of polishing process have been proposed up to now [31][32][33][34]. In this article we introduce a new possibility to use RSA technique for the modeling of plasma polishing kinetics.…”
Section: Introductionmentioning
confidence: 99%